Which is the Best Minimal Invasive Approach for the Treatment of Spontaneous Pneumothorax? Uniport, Two, or Three Ports: A Prospective Randomized Trail - Kutluk, Ali Cevat; Kocaturk, Celalettin Ibrahim; Akin, Hasan; Erdogan, Sertan; Bilen, Salih; Karapinar, Kemal; Sezen, Celal Bugra; Saydam, Ozkan (The Thoracic and Cardiovascular Surgeon, 2018)
Objective Video-assisted thoracoscopic surgery (VATS) has become the standard treatment method for primary spontaneous pneumothorax. Concerns about lesser pain and better cosmesis led to the evolution of uniportal access. This study prospectively compared the results of the uniportal, two-port, and three-port thoracoscopic surgery.Material and Methods One hundred and thirty-five patients were randomized into three groups according to the port numbers. The groups were compared regarding the operation time, hospital stay, amount of drainage, area of pleurectomy, complications, recurrences, and pain scores.Results Except for the amount of drainage (p = 0.03), no factors were found to be statistically significant. The overall recurrence rate was 5%. Although the first and second week pain scores were not statistically significant, the single-incision group patients had significantly less pain at 4, 24, and 72 hours (p < 0.05).Conclusion The study indicated that uniportal VATS approach is less painful and has better cosmetic results, besides it is as efficient as two- or three-port VATS approach.
Keywords: minimally invasive surgery; thoracoscopy/VATS; pneumothorax